Application of rebound tonometer on skin surface pressure measurement: a pilot proof of concept study - Bian, Weiwei; Ding, Wei; Yang, Lan; Wu, Ying; Huang, Ying (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundSkin tissue expansion is a widely used technique for generating additional healthy tissue to reconstruct congenital or acquired defects. Successful expansion relies on appropriate pressure management, since insufficient or excessive pressure may lead to prolonged treatment or expansion failure. Previous studies have attempted to estimate mechanical stress on expanded skin by measuring intracapsular pressure; however, this approach does not directly capture true mechanical pressure at specific skin locations. A direct method for measuring skin surface pressure remains unavailable. In this study, we evaluated the feasibility of using a rebound tonometer–a device designed for intraocular pressure measurement–for direct, site-specific assessment of skin surface pressure and for monitoring adverse events during tissue expansion.MethodsPatients with giant nevi meeting the eligibility criteria were enrolled following dilator implantation. Surface pressure measurements were obtained using the Icare® TA01i tonometer at nine predefined sites on the expanded region. The expansion protocol involved incremental saline injections of approximately 10% of the dilator’s total volume per session. At each site, pressure was recorded at three timepoints: pre-inoculation, immediately post-inoculation, and 30 min post-inoculation. Monitoring continued throughout the expansion process until the dilator reached twice its original volume.ResultsA total of five pediatric patients (2 boys and 3 girls), aged 3–6 years, were enrolled in this study. Each patient underwent a 34-day expansion period comprising eight or ten saline injections. No adverse events were recorded throughout the study. The rebound tonometer successfully detected dynamic changes in skin surface pressure corresponding to dilator volume increases. Furthermore, multi-point measurements across the expanded region confirmed the presence of spatially heterogeneous pressure distribution, demonstrating significant variations between different anatomical locations.ConclusionThis pilot study supports the technical feasibility of using a rebound tonometer for monitoring skin surface pressure dynamics during tissue expansion. The device demonstrated favorable operational efficiency, safety profile, and measurement reproducibility throughout the expansion period. These preliminary findings suggest that rebound tonometry may represent a promising monitoring approach in tissue expansion protocols, though larger-scale validation is warranted to substantiate these observations.